The Green Technology Agenda of the People's Republic of China (PRC) on Environmental Security and Health Security Issues for the People of the Democratic Republic of Congo (DRC) - Vienna Zebrina Arga, Laurensia (Sean Institute, 2025)
Journal This tries to analyze the green technology agenda against the sustainability of society and the environment in the Democratic Republic of the Congo (DRC). In facing the transformation of electricity, oil, and gas for acceleration technology and transportation in the era of the Industrial Revolution, 4.0, countries in the world need this approach to manufacturing to source natural power in a way that is feasible, sustainable, and friendly for the environment. Approach This is also known as the green technology agenda. This agenda has occurred in several countries with source power in large natural worlds, such as the Congo, which has cobalt as the material standard for the main battery. Unfortunately, the practice of mining cobalt by foreign countries, such as the People's Republic of China (PRC), has caused loss to Congolese society, starting from a degradation of the environment and bringing issues of human security. Research This study uses the library and data analysis through Glass's Green Theory. Conclusions obtained in the study Qualitative descriptive This supports the hypothesis that there is a green technology agenda that the PRC has left negative in the ecology and society of the Congo, especially in the security environment and health.